Twilight - Meyer, Stephenie, 1973-; Doobinin, Gail; Little, Brown and Company (New York : Little, Brown and Co., 2006)
When seventeen-year-old Bella leaves Phoenix to live with her father in Forks, Washington, she meets an exquisitely handsome boy at school for whom she feels an overwhelming attraction and who she comes to realize is not wholly human.
First sight -- Open book -- Phenomenon -- Invitations -- Blood type -- Scary stories -- Nightmare -- Port Angeles -- Theory -- Interrogations -- Complications -- Balancing -- Confessions -- Mind over matter -- The Cullens -- Carlisle -- The game -- The hunt -- Goodbyes -- Impatience -- Phone call -- Hide-and-seek -- The angel -- An impasse -- An occasion.
"First paperback edition: September 2006."--T.p. verso.
"Cover design by Gail Doobinin"--Back cover.
"Megan Tingley Books."
Young Adult.
720
Accelerated Reader
Keywords: Vampires -- Fiction; High school students -- Fiction; High schools -- Fiction; First loves -- Fiction; Love; Young adult fiction; Swan, Bella (Fictitious character) -- Juvenile fiction; Cullen, Edward (Fictitious character) -- Juvenile fiction; Vampires -- Juvenile fiction; High schools -- Juvenile fiction; First loves -- Juvenile fiction; Persistence -- Juvenile fiction; Friendship -- Juvenile fiction; Washington (State) -- Fiction; Washington (State) -- Juvenile fiction